Brugada syndrome, early repolarization syndrome/j-wave syndromes, and a subtype of idiopathic ventricular fibrillation: microstructural cardiomyopathies - Ricardo Pérez-Riera, Andrés (2024)
Brugada Syndrome is an inherited cardiac channelopathy with a high incidence of ventricular fibrillation and sudden cardiac death in patients with structurally normal hearts. Diagnosis is based on a characteristic electrocardiographic pattern (coved type ST-segment elevation ≥2 mm followed by a negative T-wave in ≥1 in the right precordial leads V1-V2) combined with an absence of gross structural abnormalities and several other criteria. The cornerstone of BrS diagnosis and definition, is its characteristic ECG pattern that can be present spontaneously or unmasked by drugs. This entity was described by the Brugada brothers in 1992 and belongs to a group of diseases known as inherited primary arrhythmia syndromes. The prevalence varies among regions and ethnicities, affecting mostly males. Despite several genes identified, SCN5A seems to be the most affected gene related BrS (≈ 30% of patients). The current main therapy is an implantable cardioverter-defibrillator, but radiofrequency catheter ablation has been recently reported as an effective new treatment.